Exploring science with young children : a developmental perspective - Russell, Terry, 1946-; McGuigan, Linda (SAGE, 2016)
This book supports practitioners to understand science in the early years curriculum (i.e. understanding the world) and how best to nurture key scientific skills in order to form a firm base for learning for young children aged 3-7.